FUNCTIONING OF POLICE IN VOLGOGRAD OBLAST IN THE ESTIMATIONS OF THE PUBLIC - A. P. Alekseyeva (Russian Journal of Economics and Law)
Objective: to determine the reliability and objectivity of information to the population, on the functioning of police in Volgograd oblast. Methods: sociological (absentee polling in the form of a questionnaire); statistical; logical; documentary; graphic; method of systemic analysis. Results: the opinions of the population on police are extremely controversial. It is connected mostly with the sources of information, whichmostly are not reliable and objective.The article shows that, despite the growth of victimization, the level of anxiety of the population about the criminal attacks is gradually reduced, and the sense of security in citizens is strengthened, though often due to their personal efforts (to protect their life, health and property). Only every fifth citizen relies on the participation of law enforcers in ensuring security and public order. The survey revealed that about half of the citizens, who are potentially interested in the reaction of law enforcement officers to the crime, actually agree to leave the offender unpunished due to the mistrust of the police. A third of claimants were unsatisfied with the police action on their application, which does not correlate with the declared numbers.The opinion of Volgograd citizens on the frequency of bribery among police officers remains unchanged, whereas other malfeasances received a significant increase. And, despite this, the attitude of the respondents towards the police in general has improved. Mostly it was the result of media activities that inform the public about successful police work using TV shows, documentaries and feature films. The successful work of the police is also confirmed by statistic that shows the rapid decline in recorded crime.Scientific novelty: for the first time, on the basis of a combination of various methods, the reliability and objectivity of information to the population is investigated, on the police of Volgograd oblast.Practical significance: the main provisions and conclusions of the article can be used in research and teaching in the consideration of people's assessment of the activity of modern police in Russia.